Epigenetic Approach to PTSD: In the Aspects of Rat Models - Aykac, Asli; Kalkan, Rasime (Global Medical Genetics, 2021)
Posttraumatic stress disorder (PTSD) is a stress-related mental disorder and develops after exposure to life-threatening traumatic experiences. The risk factors of PTSD included genetic factors; alterations in hypothalamic–pituitary–adrenal (HPA) axis; neurotrophic, serotonergic, dopaminergic, and catecholaminergic systems; and a variety of environmental factors, such as war, accident, natural disaster, pandemic, physical, or sexual abuse, that cause stress or trauma in individuals. To be able to understand the molecular background of PTSD, rodent animal models are widely used by researchers. When looking for a solution for PTSD, it is important to consider preexisting genetic risk factors and physiological, molecular, and biochemical processes caused by trauma that may cause susceptibility to this disorder. In studies, it is reported that epigenetic mechanisms play important roles in the biological response affected by environmental factors, as well as the task of programming cell identity. In this article, we provided an overview of the role of epigenetic modifications in understanding the biology of PTSD. We also summarized the data from animal studies and their importance during the investigation of PTSD. This study shed light on the epigenetic background of stress and PTSD.
Keywords: PTSD; epigenetics; methylation; rat studies